High‐Power Actuation from Molecular Photoswitches in Enantiomerically Paired Soft Springs - Aßhoff, Sarah J. (Angew Chem Int Ed Engl, 2017)
Motion in plants often relies on dynamic helical systems as seen in coiling tendrils, spasmoneme springs, and the opening of chiral seedpods. Developing nanotechnology that would allow molecular‐level phenomena to drive such movements in artificial systems remains a scientific challenge. Herein, we describe a soft device that uses nanoscale information to mimic seedpod opening. The system exploits a fundamental mechanism of stimuli‐responsive deformation in plants, namely that inflexible elements with specific orientations are integrated into a stimuli‐responsive matrix. The device is operated by isomerization of a light‐responsive molecular switch that drives the twisting of strips of liquid‐crystal elastomers. The strips twist in opposite directions and work against each other until the pod pops open from stress. This mechanism allows the photoisomerization of molecular switches to stimulate rapid shape changes at the macroscale and thus to maximize actuation power.